Hukum Islam: Hakikat dan Tujuan Pemberlakuan - Saidurrahman Saidurrahman (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2009)
My main intention of writing this article howefer is very simple. Mainly I want to invite participants to paya greater attention on doing further research on Islamic law from philosophy point of view. Most of the time Islamic law is studied merely based on teology perspective. Islamic law philosophy questioned problems that is beyond of ordinary law, critically questioned absolute paradigm in the Islamic law and constructively tried to unify the branchs of Islamic law in the whole of Islamic law system which is unseparable. So Islamic law philosophy offered questions about the exact meaning and the real goal of Islamic law.